Synthesis and Performance Evaluation of Magnetized Modified Coal Fly Ash as Adsorbent for Naphthol Blue Black Dye Removal from Synthetic DyeWastewater - Restu Kusumawardani; Aprilina Purbasari (TEKNIK, 2022)
The removal of dyes from wastewater has become a major concern in the textile industry due to the adverse effects of dyes on the environment. This research focuses on the adsorption of naphthol blue black (NBB) dye by synthesizing coal fly ash with alkali (sodium hydroxide solution) and Fe3O4 (magnetite) to accelerate the separation of dyes from aqueous solutions. Magnetized modified coal fly ash (MMCFA) was characterized by XRF, SEM, and FTIR analysis. Batch experiments were carried out to study the effect of pH, initial concentration, and contact time on the efficiency of dye removal. The results showed that the adsorption of NBB dye reached the optimum condition at initial concentration of 100 mg/L with pH of 6 and contact time of 120 minutes. The ability of MMCFA to adsorb NBB dye was higher than that of sieved coal fly ash (SCFA) and modified coal fly ash (MCFA). The addition of alkali and Fe3O4 can be proven to increase the adsorption ability of SCFA. The percentage of NBB dye that was adsorbed by MMCFA, MCFA, and SCFA at optimum condition was 96.39%, 89.83%, and 89.33%, respectively.